OFICINA DIDÁTICA: A QUÍMICA NA PRODUÇÃO DE PRODUTOS DE HIGIENE E BELEZA ARTESANAIS - Marques Nunes, Bruna; de Oliveira Nascimento, Daniel; Franco da Costa, Hendrick Victor; Soares Silva, Henrique; Bosso Tomal, Adriana Aparecida (Intercursos, 2026)
não há